Comment Hollywood figure l’intériorité dans les films « hollywoodiens » de David Lynch, Lost Highway (1997), Mulholland Dr. (2001) et Inland Empire (2006) - David ROCHE (E-REA)
The article takes Zachary Baqué’s study of Los Angeles in the films of David Lynch as a starting point to explore David Lynch’s Hollywood movies. The author contends that the films offer more than a satirical representation of a corrupt, unhealthy system which threatens dreams and artistic creativity, or a parodic play on Hollywood genre and narrative conventions. Rather, Hollywood is a character, a presence, revealed as both horizontal and vertical, physical and abstract, evoking the city, the studio system, cinema and dreams, so that the satire, the visual motifs and clichés and the topography of Hollywood, and the references to Hollywood films, constitute a complex fabric of subjectivity and interiority.